A facile approach to nanoarchitectured three-dimensional graphene-based Li–Mn–O composite as high-power cathodes for Li-ion batteries - Zhang, Wenyu (Beilstein-Institut, 2012)
We report a facile method to prepare a nanoarchitectured lithium manganate/graphene (LMO/G) hybrid as a positive electrode for Li-ion batteries. The Mn(2)O(3)/graphene hybrid is synthesized by exfoliation of graphene sheets and deposition of Mn(2)O(3) in a one-step electrochemical process, which is followed by lithiation in a molten salt reaction. There are several advantages of using the LMO/G as cathodes in Li-ion batteries: (1) the LMO/G electrode shows high specific capacities at high gravimetric current densities with excellent cycling stability, e.g., 84 mAh·g(−1) during the 500th cycle at a discharge current density of 5625 mA·g(−1) (~38.01 C capacity rating) in the voltage window of 3–4.5 V; (2) the LMO/G hybrid can buffer the Jahn–Teller effect, which depicts excellent Li storage properties at high current densities within a wider voltage window of 2–4.5 V, e.g., 93 mAh·g(−1) during the 300th cycle at a discharge current density of 5625 mA·g(−1) (~38.01 C). The wider operation voltage window can lead to increased theoretical capacity, e.g., 148 mAh·g(−1) between 3 and 4.5 V and 296 mAh·g(−1) between 2 and 4.5 V; (3) more importantly, it is found that the attachment of LMO onto graphene can help to reduce the dissolution of Mn(2+) into the electrolyte, as indicated by the inductively coupled plasma (ICP) measurements, and which is mainly attributed to the large specific surface area of the graphene sheets.